Taking Divination Seriously: From Mumbo Jumbo to Worldviews and Ways of Life - Sónia Silva (Religions, 2018)
The peripheral role of divination in religious studies reflects centuries of misrepresentation and depreciation in the textual record. This long history dates back to the travel literature of early modern times, particularly in West Africa, where two stereotypical themes took form: divination as mumbo jumbo, and the diviners as charlatans who shamelessly deceive their credulous clients. These two stereotypical themes persisted through the anthropological discourse about African divination until the 1970s. To undo this long history of misrepresentation and depreciation, a change of analytical focus from reified differences to similar engagement with broad ideas and big questions is in order. By considering a particular case study—basket divination in northwest Zambia—through the theoretical lens of worldviews and ways of life, it becomes possible to take divination seriously and grant it a more central place in religious studies. Four broad, inclusive ideas or big questions emerge from the ethnography of basket divination in northwest Zambia: ontology, epistemology, praxeology, and the place of suffering in human existence.